Morning glory optic nerve in Aicardi syndrome: Report of a case with fluorescein angiography. Issue 6 (November 2021) - Al-Moujahed, Ahmad; Callaway, Natalia F; Ludwig, Cassie A; Rayess, Nadim; Wood, Edward; Moshfeghi, Darius M
Background: Aicardi syndrome is an X-linked condition that is associated with multiple ophthalmic malformations. Here, we report the first published fluorescein angiography (FA) study of a morning glory optic nerve in a patient with Aicardi syndrome and contralateral persistent fetal vasculature (PFV). Case description: A 12-day old full-term baby girl with a normal neurological exam was referred for evaluation of microphthalmia. The posterior segment of the right eye demonstrated chorioretinal lacunae typical of Aicardi syndrome and microphthalmos with a stalk consistent with PFV. The right eye imaging could not be captured due to the severe microphthalmos and cataract, however, fluorescein angioscopy was performed. The left eye demonstrated a morning glory appearing optic disc with peripapillary chorioretinal lacunae. Fluorescein angiography of the eye showed and late staining in the areas of ellipsoid chorioretinal lacunae emanating from the optic nerve and extensive peripapillary staining and late leakage of the optic nerve. Conclusion: Patients with Aicardi syndrome can have morning glory optic nerve anomaly and PFV. Using FA under anesthesia to detect these abnormalities help in estimating the extend of the disease and its complications, which allows for better management of the complications.